A developmental approach to diglossia: Bilectalism on a gradient scale of linguality - Grohmann, Kleanthes K.; Kambanaros, Maria; Leivada, Evelina; Rowe, Charley (My University, 2016)
The cognitive benefits of bilingualism have an impact on the processing mechanisms that are active during the acquisition process in a way that results in language variation. Within bilingual populations, the notion of "language proximity" is also of key importance for deriving variation. Certain sociolinguistic factors can invest the process of language development and its outcome with an additional layer of complexity that results from the emergence of mesolectal varieties which blur the boundaries of grammatical variants. We report data on the acquisition and development of object clitic placement in the two varieties of Greek spoken in Cyprus, and on performance in executive control tasks by monolingual, bilectal, and bi-/multilingual children. Comparing findings across experiments, the present study identifies the different factors that define "bilectalism" within the greater context of multilingualism, merging sociolinguistic and neurocognitive insights about language variation and how they inform development in diglossic contexts that involve closely related varieties - a study in comparative linguality.
Keywords: Bilectalism; Clitics; Executive control; Mesolect; Multilingualism